Development of universal vacuum gripper for wall-climbing robot. (19th March 2018) - Fujita, Masahiro; Ikeda, Suguru; Fujimoto, Toshiaki; Shimizu, Toshihiko; Ikemoto, Shuhei; Miyamoto, Takeshi
Abstract: Task performed at a height, such as wall inspections are one of the dangerous tasks for humans. Thus, robotic technology for safety inspection is required. This research focuses on developing robots to climb vertical walls with flat and uneven surfaces, e.g. concrete, tile and riveted structure. To have wall-climbing capability, climbing robots use vacuum pads, claws, magnets, intermolecular force, and adhesive. However, each of these approaches has disadvantages. To achieve wall climbing on an uneven surface without scratching and staining, we have developed a novel vacuum pad named the Universal Vacuum Gripper (UVG), which is based on the Universal Gripper (UG). The UG is a robot hand using jamming transition of coffee powder inside a balloon to grip uneven material. The UVG is a vacuum pad with a deformable skirt based on the UG. If the skirt shape is deformed in accordance with the contact surface, air leaks can be avoided. Moreover, the deformed skirt can be stiffened, thereby working as a gripper. Here, we evaluate the proposed gripper, having both grasping and adhesion force. We also develop a wall-climbing robot with UVGs, and evaluate its performance on uneven surfaces under real-world conditions. Abstract :